2021
DOI: 10.53333/ijicc2013/15303
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Productive Zakat for Reducing Urban Poverty in Indonesia

Abstract: Productive zakat is a strategic mechanism to help alleviate poverty. This study aims to explore the mechanism by which BAZNAS manages productive zakat in an attempt to help alleviate poverty in Indonesia. This study uses a qualitative exploratory approach. Documentary data pertaining to zakat distribution to mustahīq in the urban poor Surabaya was collected from the East Java BAZNAS office. Several interviews with the leaders of this office were also conducted to capture their views on the management of produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
(21 reference statements)
2
2
0
Order By: Relevance
“…Besides, 68.7% face social stigma and 72.7% harassment, signaling continuing disempowerment despite modest legal knowledge gains (43.7% to 68.6%). This aligns with evidence that reduced societal value assigned to women's informal work spreads inequities (Nisak & Sugiharti, 2020; Crain, 1995) [44,14] . The multifaceted vulnerabilities confronting marginalized working women in the informal sector (UNWomen, 2022; Addati et al, 2018) [1] .…”
Section: Analysis and Discussionsupporting
confidence: 79%
“…Besides, 68.7% face social stigma and 72.7% harassment, signaling continuing disempowerment despite modest legal knowledge gains (43.7% to 68.6%). This aligns with evidence that reduced societal value assigned to women's informal work spreads inequities (Nisak & Sugiharti, 2020; Crain, 1995) [44,14] . The multifaceted vulnerabilities confronting marginalized working women in the informal sector (UNWomen, 2022; Addati et al, 2018) [1] .…”
Section: Analysis and Discussionsupporting
confidence: 79%
“…This means that material poverty can be reduced to 62%. The results of the calculation of the material and spiritual welfare of zakat recipients using the CIBEST Welfare Index come in at a score of 4, which means that based on the CIBEST index it is in the range of 0.61-0.80 or good, The results of this study are supported by research conducted by Kholis 2021 [30], Arifin, 2021 [31], and Sapingi 2018 [32] which examines the impact of zakat on the welfare of zakat recipients, although it does not specifically measure the welfare of recipients of entrepreneurship programs but it is concluded that zakat programs with the CIBEST model can reduce poverty of zakat recipient. Furthermore, to see the increase in the value of the mustahiq material based on the impact of zakat which is influenced by other elements, before providing assistance, a survey and confirmation is carried out to prospective recipients of zakat assistance to find out whether the prospective recipients of entrepreneurship program funds are eligible to receive financial assistance or not.…”
Section: Results and Analysissupporting
confidence: 66%
“…Moreover, ILO (2018) and Moreira da Silva (2019) also reinforced that the proportion of women as unpaid workers is 76.2 percent at the global level, which is 3.2 times greater than un-paid men. Discrimination on the basis of gender inequality limits women's access to rights at work and increases socioeconomic vulnerability (Nisak et al, 2020). The results in Table 9 unveiled that 37.3 percent of the respondents reported that the social factors caused gender disparity in the context of access to rights at work and made them vulnerable workers.…”
Section: Resultsmentioning
confidence: 97%